Upper Homerian (Wenlock, Silurian) graptolites and graptolite biostratigraphy, Arctic Archipelago, Canada - Lenz, Alfred C. (Canadian Journal of Earth Sciences, 1995)
Integration of graptolite data obtained from isolated and flattened material from Arctic Canada permits the recognition of three upper Homerian biostratigraphic zones. These, from oldest to youngest, are the Pristiograptus dubius – Gothograptus "nassa" interval Biozone, Colonograptus? praedeubeli – Colonograptus? deubeli Biozone, and Colonograptus? ludensis Biozone. Species of flattened graptolites described in this study include C.? deubeli, C.? ludensis, C.? praedeubeli, Colonograptus? schedidoneus,Lobograptus ? angustus n.sp., Lobograptus? claudiae, Lobograptus? sherrardae, Plectograptus macilentus, Agastograptus clathrospinosus, and Gothograptus "nassa." With only a few exceptions, the zone-by-zone diversity of monograptid and plectograptine graptolites of the Canadian Arctic is remarkably similar to that elsewhere.